Metal composite as backing for ultrasonic transducers dedicated to non-destructive measurements in hostile. Issue 1 (January 2016) - Boubenia, R; Rosenkrantz, E; Despetis, F; P, P; Ferrandis, J-Y
Abstract: Our team is specialized in ultrasonic measurements in hostile environment especially under high temperatures. There is a need for acoustic transducers capable of continuous measurement at temperatures up to 700°C. To improve the performances of acoustic sensors we focus our works on the realisation and characterisation of transducer backings able to operate under very high temperature. Commercially, they are produced by the incorporation of tungsten powder in a plastic matrix, which limits the working temperature. The realisation of ultrasonic transducers for non-destructive measures at high temperatures requires adequate materials, manufacturing and assembly processes. To produce the backings, composites were made using very ductile metals such as tin and tungsten. These composites are manufactured by uniaxial hot pressing. First, we studied the influence of temperature and pressure on the densification of tin pellets. Then, several specimens made of tin/W were made and characterised by measuring the specific weight, speed and attenuation of sound. The acoustic measures were realised by ultrasonic spectroscopy. This test-bench was designed and tested on control samples of PMMA and on standard backings (epoxy / tungsten).